E-Infrastructure and e-Services for developing countries : 6th International Conference, AFRICOMM 2014, Kampala, Uganda, November 24-25, 2014, Revised selected papers /: 6th International Conference, AFRICOMM 2014, Kampala, Uganda, November 24-25, 2014, Revised selected papers. (2015) - Unknown
No abstract available